Pemilihan Karier Akuntan Publik : Pengaruh Orientasi Etika, Gender, Umur dan Tingkat Pengetahuan - Prasetya, Mario Bayu; Baridwan, Zaki (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to examine the factors that influence accounting students in selecting public accountants career using a model that developed by Comunale et al in 2006. The sample was accounting students who have taken courses in Auditing 1, number of 274 students of Department of Accounting, Faculty of Economics and Business, University of Brawijaya, Malang. The results of the analysis for this model shows that the construct of idealism influence on the selection of public accounting career by accounting students. Whereas, relativism, gender, age, and level of knowledge about the profession of public accountants and accounting scandals did not influence the selection of accounting career by accounting students. The implications of this study are relevant for academics in the Department of Accounting Faculty of Economics and Business in order to stay instilling moral values ââand ethics to students to produce a prospective public accountants who are ethical, professional, and idealistic. Keywords: idealism, relativism, gender, age, level of knowledge, career choice, accounting student